Comparative study of gammagraph and echography: for the determination of the presence of cancer in a thyroid nodule - Delgado, Bolívar; Cluzet, Oscar; Yametti, Luis (Cirugía del Uruguay, 1984)
The gammagraphic and echographic methods are compared as to their respective value in the determination of whether a thyroid nodule may be a cancer, concluding that lhe latler is significantly superior, beign surpassed only oy a combination of the two methods.